ASUHAN KEPERAWATAN PADA PASIEN GAGAL GINJAL KRONIK DENGAN HEMODIALISA MELALUI TINDAKAN KOMPRES DINGIN PADA AV SHUNT - Rahma, Nur; Jundapri, Kipa; Susyanti, Deni; Suharto, Suharto (LPPM Institut Pendidikan Nusantara Global, 2023)
Hemodialysis is an intervention designed to assist patients in managing fluid and electrolyte metabolism. The hemodialysis process involves puncturing the arteriovenous (AV) shunt area to facilitate dialysis. The repeated punctures in this area can result in pain. Research Objective: To provide an overview of nursing care for chronic kidney failure patients undergoing hemodialysis through the use of cold compresses on the AV shunt site. Method: This study is a case study with a medical-surgical nursing care approach. The research was conducted from February to March 2023 on two chronic kidney failure patients undergoing hemodialysis. Results and Discussion: After the intervention of applying cold compresses to patients I and II, a reduction in pain scale was observed. For patient I, the pain scale decreased from 6 (0-10) before the intervention to 3 (0-10) after the intervention. For patient II, the pain scale decreased from 5 (0-10) to 3 (0-10) after the intervention. Conclusion and Recommendations: Cold compresses can effectively reduce pain at the AV shunt puncture site in hemodialysis patients. Therefore, it is recommended to incorporate cold compress interventions for patients undergoing hemodialysis.